2018
DOI: 10.1371/journal.pntd.0006877
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence for the tick-borne relapsing fever spirochete Borrelia turicatae among small and medium sized mammals of Texas

Abstract: BackgroundIn low elevation arid regions throughout the southern United States, Borrelia turicatae is the principal agent of tick-borne relapsing fever. However, endemic foci and the vertebrate hosts involved in the ecology of B. turicatae remain undefined. Experimental infection studies suggest that small and medium sized mammals likely maintain B. turicatae in nature, while the tick vector is a long-lived reservoir.Methodology/principal findingsSerum samples from wild caught rodents, raccoons, and wild and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…and the pathogenic potential of relapsing fever Borrelia for other vertebrates, including humans, the question of the extent of the circulation of such bacteria arises. Given the growing interest in relapsing fever Borrelia in America and the biomedical tools that may become available to detect the past exposure of hosts by tracking antibody levels (Lopez et al, 2013), investigations could rely on the detection of the Borrelia in ticks, but also sometime more efficiently by detecting antibodies in the vertebrate host (Armstrong et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…and the pathogenic potential of relapsing fever Borrelia for other vertebrates, including humans, the question of the extent of the circulation of such bacteria arises. Given the growing interest in relapsing fever Borrelia in America and the biomedical tools that may become available to detect the past exposure of hosts by tracking antibody levels (Lopez et al, 2013), investigations could rely on the detection of the Borrelia in ticks, but also sometime more efficiently by detecting antibodies in the vertebrate host (Armstrong et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Field studies should be focused at the suspected exposure site to collect serum samples from small and medium-sized mammals, including rodents and domestic and wild canids. These mammals likely have a role in the ecology of TBRF spirochetes [17]. Furthermore, while most Ornithodoros sp.…”
Section: Case Discussionmentioning
confidence: 99%
“…In support of this, O. turicata ticks have been collected in dens and caves frequented by coyotes [5]. Furthermore, a serosurveillance study indicated grey foxes and coyotes are likely involved in the spirochete's ecology [14]. Sera was acquired from terminally sampled animals and antibody reactivity was determined to B. turicatae protein lysates and the Borrelia immunogenic protein A (BipA) [14], a diagnostic antigen used for TRBF spirochetes [39,40].…”
Section: Discussionmentioning
confidence: 98%
“…In Texas, B. turicatae was isolated from field collected ticks, sick domestic canines, and a soldier that was conducing field exercises in the state [12,13]. There have also been case studies for the distribution of B. turicatae in rural areas of Texas [9,14,15]. In Florida, spirochetes have been isolated from sick canines in the 1990s [12,16], but little work has followed up on those studies.…”
Section: Introductionmentioning
confidence: 99%